Complementiser and Relativiser in the English Subordinate Clauses - Mas Indrawati, Ni Luh Ketut (Lingual Journal of Language and Culture; Vol 3 No 1 (2017), 2017)
Words combine to form larger units; phrases, clauses, and sentences. The study of the structure of phrases, clauses, and sentences is referred to as syntax. Quirk, et, all (1985:47) distinguishes sentences into two types they are; simple sentences and multiple sentences which cover compound sentences and complex sentences. A simple sentence consists of one independent clause, a multiple clause contains more than one clauses, a compound sentence consists of two or more independent clauses, while a complex sentence consists of insubordinate and subordinate clauses. Subordinate clause, in embedding the element of the insubordinate clause use either complementiser or relativiser. For example: (1) john said that he did not come to the party. That in (1) is considered to be complimentiser since it introduces the subordinate clause. (2) John met the teacher that teaches you English. That in (2) is classified as relativiser because it is used to introduce the modifying clause. This paper attempts to discuss complementiser and relativiser in the English subordinate clauses and describe the constituent structure in a tree diagram using the approach proposed by Kroeger (2005). The data were taken from a novel entitled Saved by The Bride by Fiona Lowe (2013). Keywords: complex sentences, subordinate clauses, complementiser or relativiser